Abdominal Obesity Phenotypes and Incidence of Thyroid Autoimmunity: A 9-Year Follow-up. (2nd July 2020) - Amouzegar, Atieh; Kazemian, Elham; Abdi, Hengameh; Gharibzadeh, Safoora; Tohidi, Maryam; azizi, Fereidoun
ABSTRACT: Purpose: The association between obesity and autoimmune diseases has been suggested by several previous studies. The objective of our study was to assess the association of abdominal obesity phenotypes with thyroid autoimmunity. Materials and methods: This study was conducted within the framework of a population-based cohort study, Tehran Thyroid Study (TTS) on 4708 subjects without thyroid autoimmunity at baseline. Participants were categorized into four abdominal obesity phenotypes according to waist circumference (WC) and other metabolic syndrome components. Serum concentrations of thyroid peroxidase antibody (TPOAb), free T4 (FT4), thyrotropin (TSH), glucose, and lipid profiles were measured after 3, 6 and 9 years of follow-up. Cox proportional hazard models were used to evaluate associations of different phenotypes with the incidence of thyroid autoimmunity, adjusted for age, sex, FT4, and TSH. Results: Highest and lowest incidence rates of TPOAb positivity were observed among metabolically unhealthy, non-abdominally obese (MUNAO) [8.78 (7.31–10.55) per 1000 person-years of follow-up] and metabolically unhealthy abdominally obese (MUAO) [4.98 (3.88–6.41) per 1000 person-years of follow-up] phenotypes. Considering the metabolically healthy non-abdominal obese (MHNAO) individuals as reference, none of metabolically healthy abdominally obese (MHAO), MUNAO, and MUAO phenotypes were associated with increased risk of developing TPOAb positivity. Compared to individuals with high WC, the incidence rate (95%CI) of TPOAb positivity was higher among those with normal WC: 8.44 (7.13–10.0) vs 5.11 (4.01–6.51) per 1000 person-years, respectively. Higher WC was not associated with incident TPOAb positivity. Conclusion: There was no significant association between baseline abdominal obesity phenotype status and development of TPOAb positivity over 9 years of follow-up.